2018
DOI: 10.1002/nau.23904
|View full text |Cite
|
Sign up to set email alerts
|

Defecation disorders in Spina Bifida: Realistic goals and best therapeutic approaches

Abstract: Aims Spina Bifida (SB) is a rare congenital condition that frequently impairs the neurological control of both fecal continence and defecation. Several therapeutic strategies have been proposed but impact assessment is lacking. Our objectives were to quantify the symptomatic improvement and to determine the optimal strategy in this rare condition where randomized controlled trials are difficult to conduct. Methods Data were extracted from a prospective database. The present analysis focused on patients having … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Hence, the maximum score for randomised trials was 28 and non-randomised studies 25. Studies were classified as being excellent (26)(27)(28), good (20)(21)(22)(23)(24)(25), fair (15)(16)(17)(18)(19) or poor (≤14) [18]. The assessment was independently performed by two reviewers (H.Ø.K.…”
Section: Risk Of Bias and Quality Assessmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Hence, the maximum score for randomised trials was 28 and non-randomised studies 25. Studies were classified as being excellent (26)(27)(28), good (20)(21)(22)(23)(24)(25), fair (15)(16)(17)(18)(19) or poor (≤14) [18]. The assessment was independently performed by two reviewers (H.Ø.K.…”
Section: Risk Of Bias and Quality Assessmentmentioning
confidence: 99%
“…In total, eleven studies were identified reporting data on the effect of TAI in NBD patients [7,[19][20][21][22][23][24][25][26][27][28]. The results are presented in Table 1.…”
Section: Neurogenic Bowel Dysfunctionmentioning
confidence: 99%
See 3 more Smart Citations